FCGR3A F158V alleles frequency differs in multiple myeloma patients from healthy population - Michaël Constantinides; Nicolas Robert; Caroline Multrier; Loïs Coënon; Mauricio Campos-Mora; Carine Jacquard; Fei Gao; Sara Zemiti; Jessy Presumey; Guillaume Cartron; Jérome Moreaux; Martin Villalba (OncoImmunology)
FCGR3A presents a single nucleotide polymorphism at location 158 (V/F), which affects its binding to the fragment crystallizable (Fc) of antibodies (Abs). FcγRIIIa-158 V allotype has the highest affinity and is associated with a better clinical response to IgG1 monoclonal Abs (mAb) treatment. We compared the allele frequency of FCGR3A-F158V polymorphism in cohorts of patients with B-cell lymphoproliferative disorders, including multiple myeloma (MM), monoclonal gammopathy of undetermined significance (MGUS), non-Hodgkin lymphoma (NHL), and B-cell chronic leukemia (B-CLL). FCGR3A-158F homozygous were enriched and tended to be in MM and MGUS patients, respectively; but neither in B-CLL nor in NHL patients. We identified a significantly lower concentration of CD8 T-cells and resting memory CD4 T-cells in MM patients bone marrow with the F/F genotype, associated with an increase in the macrophage percentage. In contrast, natural killer cells increased in V/V homozygous patients. This suggests a deregulation of the immune microenvironment in FCGR3A-F/F homozygous patients. However, we did not observe difference in response following treatment combining chemotherapy associated or not with daratumumab, an IgG1 mAb direct against CD38. Our findings suggest that FCGR3A F158V polymorphism can regulate the immune environment and affect the development of tumor plasma cells.